Storytelling to improve healthcare worker understanding, beliefs, and practices related to LGBTQ + patients: A program evaluation. (February 2022) - Long, Amanda; Jennings, Jacky; Bademosi, Kehinde; Chandran, Aruna; Sawyer, Simone; Schumacher, Christina; Greenbaum, Adena; Fields, Errol L.
Highlights: Examined whether storytelling events changed health care workers understanding and practices related to LGBTQ + patients. Analyzed surveys of HCW to measure differences in understanding, beliefs, and practices. Used thematic analysis to explore written feedback/notes obtained as part of a reflective exercise at storytelling events. Themes from written feedback/notes included improved understanding and new approaches for engaging LGBTQ + patients. Attending an event was associated with more favorable beliefs and practices related to LGBTQ + patients. Abstract: LGBTQ + persons experience significant health inequities and medical distrust resulting from anti-LGBTQ + bias or cultural incompetence from health care workers (HCW). This program evaluation examined whether storytelling events where LGBTQ + persons shared personal and patient experiences changed HCW understanding, beliefs, and practices related to LGBTQ + patients. Five storytelling events, held biannually in Baltimore, Maryland from 2016 to 2018, were evaluated using post-event surveys, written reflections/notes during the event, and a survey of HCW in a citywide care collaborative focused on HIV prevention and treatment for LGBTQ + persons that did and did not attend a storytelling event. We analyzed surveys to measure differences in understanding, beliefs and practices and used thematic qualitative analysis of written reflections/notes from the storytelling events. 416 persons attended storytelling events; 124(30 %) completed post-event surveys and 449 written reflections/notes were collected. 56 HCW completed post-event surveys; 49(87.5 %) strongly agreed/agreed they better understood LGBTQ + patients. Emergent themes from the 43 HCW written reflections/notes included improved understanding and new approaches for engaging LGBTQ + patients. Among HCW survey respondents (n = 111), attending an event was associated with significant differences in beliefs (p = 0.024) and practices (p = 0.000) related to LGBTQ + patients. Storytelling events may serve as effective tools for increasing HCW's understanding, beliefs and practices. This strategy may ultimately help decrease anti-LGBTQ + bias, reduce medical distrust and lower barriers to HIV prevention/treatment for LGBTQ + persons.